Prevalence of vitamin B12 deficiency in type 2 diabetic patients taking metformin, a cross-sectional study in primary healthcare - Al Quran, Thekraiat; Khader, Ateka; Allan, Hadeel; Al-Momani, Rua’a; Aqel, Hamzeh T.; Alsaleh, Mu’taz; Bataineh, Ziad (Frontiers in Endocrinology, 2023)
Background: Several studies documented that metformin use contributes to vitamin B12 deficiency in patients with type 2 diabetes mellitus (T2DM). However, there has been a lack of data assessing this issue in Jordan.Aims: Assess the vitamin B12 serum levels, frequency of vitamin B12 deficiency, and related factors among Jordanian patients with T2DM patients treated with metformin.Methods: a total of 447 subjects attending a primary health care center were included in this crosssectional study consisting of T2DM patients who use metformin and a control group of non-diabetics. Serum B12 levels were evaluated and B12 deficiency was defined as serum B12 levels ≤ 200 pmol/L. Associations of B12 serum levels or B12 deficiency with other factors like gender, age, and duration of T2DM were analyzed.Results: There was no significant difference in serum B12 levels nor the frequency of vitamin B12 deficiency between T2DM metformin-treated patients and control groups. Among metformin-treated patients there was no difference relating to age, type 2 diabetes mellitus duration, proton pump inhibitors use, and metformin use (duration, dose) between patients with or without B12 deficiency.The prevalence of vitamin B12 deficiency among T2DM patients on metformin treatment in this study was high (48.9%). However, the treatment with metformin and the dose of metformin use was not associated with vitamin B12 deficiency.